Pengaruh Persepsi Kemudahan Penggunaan, Kualitas Layanan, Dan Keamanan Terhadap Minat Perilaku Penggunaan Pada Bri Mobile (Brimo) - Yansyah, Medi; Army, M. Noor; Waliamin, Janusi (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to examine the influence of perceived ease of use, service quality, and security on the intention to use the BRImo digital banking application among students at Universitas Hazairin Bengkulu. The method used was a survey with a Likert-scale questionnaire distributed to 120 respondents to collect data regarding their experiences and perceptions of the BRImo application. The data were analyzed using multiple linear regression to test the relationships and effects of these variables on the behavioral intention to use the application. The results show that the three independent variables—perceived ease of use, service quality, and security—have a positive and statistically significant effect on the intention to use the application, with a significance value of p < 0.05. Perceived ease of use contributed significantly with a t-value of 20.613, service quality had the highest contribution with a t-value of 29.942, while security also had a significant effect with a t-value of 4.972. The coefficient of determination (R²) of 0.926 indicates that approximately 92.6% of the variation in the intention to use the BRImo application can be explained by these three variables. Although the application is generally considered easy to use and provides quality service, aspects such as responsiveness, empathy towards users, and protection of personal data still need improvement to maintain user loyalty and enhance trust sustainably. This study emphasizes the importance of optimal management of these three aspects to increase user satisfaction and encourage ongoing intention to use BRImo. The findings are expected to serve as a foundation for developers and marketers in formulating more effective strategies for application development and service improvement in the future.